Protective Coating Performance on Industrial Components During Shutdown Maintenance - Toni Okviyanto; Agus Subeno; Dibyo Setiawan; Fauzi Widiawati; Edward Simanjuntak; Otong Jaelani (Jurnal Konversi Energi dan Manufaktur, 2026)
Corrosion protection is a critical aspect of industrial maintenance because coating quality directly influences equipment durability, operational reliability, and long-term maintenance efficiency. However, coating assessments in industrial practice often focus on compliance with thickness specifications without comprehensively evaluating the relationship between surface preparation quality, environmental conditions, coating thickness, and final coating performance under actual shutdown maintenance conditions. This study aimed to evaluate the effectiveness of the coating process during total plant shutdown (TPS) painting work on four industrial components: the sole plate sag mill, cover motor ball mill, base frame motor bubble crusher, and OHC girder. A field-based coating performance assessment was conducted using final painting reports, visual inspection records, environmental condition monitoring, surface preparation evaluation, and dry film thickness (DFT) measurements. Surface preparation was carried out using ST 3/SSPC-SP 3 mechanical cleaning, while coating performance was evaluated against the specified DFT requirements. The results showed that all inspected components satisfied the acceptance criteria, with primer DFT values exceeding 150 µm and final DFT values exceeding the minimum system requirement of 225 µm. Final coating thickness increased by 263–347 µm compared to the existing condition, indicating the formation of a protective coating layer. Nevertheless, noticeable thickness variations among measurement locations suggest opportunities for improving application consistency and process control. These findings demonstrate that the applied coating system met the specified performance requirements and provided effective corrosion protection under field conditions, while further optimization of coating application practices is required to achieve more uniform and efficient coating performance.